2011 International Electron Devices Meeting 2011
DOI: 10.1109/iedm.2011.6131665
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of MOSFET-like on-current performance in arsenide/antimonide tunnel FETs with staggered hetero-junctions for 300mV logic applications

Abstract: Type II arsenide/antimonide compound semiconductor with highly staggered GaAs 0.35 Sb 0.65 /In 0.7 Ga 0.3 As hetero-junction is used to demonstrate hetero tunnel FET (TFET) with record high drive currents (I ON ) of 190µA/µm and 100µA/µm at V DS =0.75V and 0.3V, respectively (L G =150nm). In x Ga 1-x As (x=0.53, 0.7) homo-junction TFETs and GaAs 0.5 Sb 0.5 /In 0.53 Ga 0.47 As hetero TFET with moderate stagger are also fabricated with the same process flow for benchmarking. Measured and simulated TFET performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 2 publications
1
77
0
Order By: Relevance
“…As the SS of a MOSFET is governed by the transport mechanism of thermionic-emission over a thermal barrier and limited to 60 mV/dec at 300 K, further scaling down of Si MOSFET supply voltage becomes difficult without significantly increasing the OFF-state current (I OFF ). In order to control the rapidly increasing power dissipation of a conventional MOSFET, the tunnel field-effect transistor (TFET) [1][2][3][4][5][6][7][8][9][10][11][12] has been proposed as an alternative switching device in recent years. The TFET device is a reverse biased gated p þ -i-n þ diode, which exploits the gate-controlled band-toband tunneling (BTBT) mechanism to overcome the fundamental kT/q thermodynamic limit of SS in a conventional MOSFET.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the SS of a MOSFET is governed by the transport mechanism of thermionic-emission over a thermal barrier and limited to 60 mV/dec at 300 K, further scaling down of Si MOSFET supply voltage becomes difficult without significantly increasing the OFF-state current (I OFF ). In order to control the rapidly increasing power dissipation of a conventional MOSFET, the tunnel field-effect transistor (TFET) [1][2][3][4][5][6][7][8][9][10][11][12] has been proposed as an alternative switching device in recent years. The TFET device is a reverse biased gated p þ -i-n þ diode, which exploits the gate-controlled band-toband tunneling (BTBT) mechanism to overcome the fundamental kT/q thermodynamic limit of SS in a conventional MOSFET.…”
Section: Introductionmentioning
confidence: 99%
“…The TFET device is a reverse biased gated p þ -i-n þ diode, which exploits the gate-controlled band-toband tunneling (BTBT) mechanism to overcome the fundamental kT/q thermodynamic limit of SS in a conventional MOSFET. 2,3 Great efforts have been devoted to boost the performance of TFETs, such as reducing SS, [4][5][6] improving ON-state current (I ON ), 7,8 and lowering I OFF . 9,10 Recently, steep SS of <60 mV/dec was demonstrated in a III-V TFET.…”
Section: Introductionmentioning
confidence: 99%
“…7 It has been reported that reducing E beff from 0.5 eV to 0.25 eV results in at least 200% improvement of I ON in mixed As/Sb heterojunction TFETs due to the increase of tunneling transmission coefficient. 6,7 On the other hand, the reduced E beff also improves the drain induced barrier thinning (DIBT) due to the fact that the inter band generation process occurs closer to the source/channel junction, thus improving electrostatics of devices. 11 Nevertheless, if E beff < 0, a broken bandgap lineup will occur at the source/channel heterointerface.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Among these heterostructures, mixed As/Sb based heterojunction enables a wide range of staggered band lineups depending on the alloy compositions in the source and channel materials. 6,7 The band offset of the staggered gap heterojunction at the source/channel heterointerface also defines the effective tunneling barrier height (E beff ), which not only determines the ON-state tunneling current, but also sets the blocking barrier of OFF-state leakage. 5,7,10 Therefore, efforts have been devoted to optimize the band offset to boost I ON and suppress I OFF ; 6,7,10 however, to our knowledge, there is no prior report of experimental demonstration of band offset on mixed As/Sb type-II staggered gap heterojunction n-channel tunnel FET structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation